2006
DOI: 10.1542/peds.2004-2709
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Prevalence of Asthma and Allergies Among Children and Adolescents in Italy: 1994–2002

Abstract: The results indicate that the epidemiologic features of asthma and allergies in Italy are changing rapidly, although the causes are still uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
126
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 23 publications
15
126
2
4
Order By: Relevance
“…Often, it is found that rhinitis prevalence increases faster than asthma prevalence, which was also found to decrease in some countries (904,947,948,1896,(1917)(1918)(1919)(1920)(1921)(1922). It appears that in regions of highest prevalence, the proportion of subjects suffering from asthma or rhinitis may be reaching a plateau (1919).…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%
“…Often, it is found that rhinitis prevalence increases faster than asthma prevalence, which was also found to decrease in some countries (904,947,948,1896,(1917)(1918)(1919)(1920)(1921)(1922). It appears that in regions of highest prevalence, the proportion of subjects suffering from asthma or rhinitis may be reaching a plateau (1919).…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%
“…Vergleichbare Prävalenzen ärztlicher Allergiediagnosen hatten andere europäische Länder für 6-bis 7-Jährige verzeichnet, z. B. Spanien für Asthma bronchiale mit 6 % [12], Österreich für Asthma bronchiale mit 5 % und für Neurodermitis mit 14 % [13] sowie Italien für Heuschnupfen mit 9 % [14]. In der bislang größten internationalen Studie zu allergischen Erkrankungen bei Kindern und Jugendlichen, der International Study of Asthma and Allergy in Childhood (ISAAC), lag Deutschlandbezogen auf 13-bis 14-Jährige -bei der Häufigkeit von Symptomen innerhalb des letzten Jahres für Asthma bronchiale im oberen Drittel, für Heuschnupfen und Neurodermitis im Mittelfeld der untersuchten Länder [15].…”
unclassified
“…Allergic rhinitis (AR) is a very common disease that affects up to 40% of children (1)(2)(3) and, particularly in moderate to severe cases, is associated with a significant reduction in the patients' quality of life, sleep disorders, emotional problems, and impaired school productivity and social functioning. Moreover, the chronic inflammatory process caused by AR favors the development of comorbidities, increases the incidence of ear problems such as acute otitis media (AOM) and otitis media with effusion (OME), and aggravates physiological adenoid and tonsil hypertrophy in the first years of life.…”
mentioning
confidence: 99%